2014
DOI: 10.1136/neurintsurg-2014-011181.rep
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular coil retrieval using a TrevoProVue stentriever

Abstract: A 65-year-old man with a left cavernous internal carotid artery cerebral aneurysm experienced a premature detachment of the first framing coil (10 mm×40 cm Penumbra Complex Standard) during a coil embolization procedure. The coil herniated into the anterior cerebral artery and pericallosal artery. Multiple attempts to retrieve the coil using both a 2 and 4 mm Microsnare (Amplatz GooseNeck) failed. A Trevo ProVue retrievable stent was then used to retrieve the coil without any adverse events. This case report h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“… 7 Coil retrieval in patients has been reported with various stent retrievers, namely the Solitaire, the Trevo ™ (Stryker, Kalamazoo, MI) and the Catch device (Balt, Montmorency, France), and was successful in all 19 reported cases. 3 6 , 8 While all published cases were dealt with intracranial coils, we also showed that it is possible to recover a small coil in a peripheral artery with a small diameter. In summary, coil retrieval with stent retrievers can be considered an effective treatment option in a vast variety of settings.…”
Section: Discussionmentioning
confidence: 54%
“… 7 Coil retrieval in patients has been reported with various stent retrievers, namely the Solitaire, the Trevo ™ (Stryker, Kalamazoo, MI) and the Catch device (Balt, Montmorency, France), and was successful in all 19 reported cases. 3 6 , 8 While all published cases were dealt with intracranial coils, we also showed that it is possible to recover a small coil in a peripheral artery with a small diameter. In summary, coil retrieval with stent retrievers can be considered an effective treatment option in a vast variety of settings.…”
Section: Discussionmentioning
confidence: 54%
“…Kabbani et al 11 reports a case of a prematurely detached coil migrated into the left pericallosal artery, in which after previous failed attempts with Microsnares, a Trevo ProVue® was used to successfully retrieve the coil in 2 passes. Similarly, Nas et al 12 presented another case of a partially protruding coil being retrieved with a Solitaire® device after 3 passes, with no mention of the device construction in its ability to successfully retrieve the coil.…”
Section: Discussionmentioning
confidence: 99%
“…[6,7] The stent retriever Trevo ProVue (Stryker, Kalamazoo, Michigan, USA), which is indicated for thrombectomy during acute ischemic strokes, has also been used for foreign body retrieval. [8]…”
Section: Discussionmentioning
confidence: 99%
“…[4] Various options exist to resolve this complication. [5-8] We report one additional option that has already been described for peripheral use but never for the retrieval of a foreign body that has migrated to the brain through a transradial approach.…”
Section: Introductionmentioning
confidence: 99%